Pivotal Issues of Democratic Governance: A Literature Review - Ulung Pribadi; Muhammad Iqbal (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
Democratic governance has become a popular term to influence public sector reform in many countries. As a new governance theory, democratic governance has also gained significant interest from scholarly circles. Scholars had different perspectives when discussing the topic of democratic governance. Political perspectives examined democratic governance, especially in terms of states, regime, election and democracy. Technological perspective saw the importance of ICTs, social media, artificial intelligence and big data. The public administration perspective studied the importance of public policy, public management and local government institutions. There were rarely scholars who mapped the ideas about democratic governance. The study tries to fill this gap in thinking about democratic governance by reviewing the journal articles on democratic governance published in Scopus data based. Via NVivo analysis tools, this study showed five pivotal issues, including “government,” “public,” “policy,” “political,’ and ‘institutional.’ Besides, this study revealed some important sub-issues of the pivotal issues, covered ‘responsible government,” “representative government,” “government policy,” “public participation,” “public affairs,” “public interest,” “public policy,” “policy formulation,” “policy implementation,” “political participation,” “political actors,” “political authority,” “institutional change,” “institutional capacity,” “state institutions.’ This study also developed propositions from the pivotal issues and sub-issues. Furthermore, this study proposed a new theoretical model based on the propositions. Finally, this study acknowledges the weaknesses and suggests future research.